(untitled) (Global Journal of Science Frontier Research, 1969)
We have developed a new model to study the structural, mechanical and thermal properties of SrS 1-x Se x , SrS 1-x Te x and SrSe 1-x Te x ternary alloys. This model includes the Coulomb interaction, TBI interaction, vander Waal interaction overlap repulsive interactions extended up to the second neighbour ions and covalent interaction. The variation of Gibb’s free energy, phase transition pressure and the bulk modulus from the concentration using Vegard’s law were observed for the three alloys. Our calculated results have revealed reasonably good agreement with the available experimental data on the phase transition pressures and volume collapse. In addition we have calculated other mechanical and thermal properties.